2013
DOI: 10.1371/journal.pone.0077902
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Birdwatchers’ Playback Affects the Behavior of Two Tropical Birds

Abstract: Although recreational birdwatchers may benefit conservation by generating interest in birds, they may also have negative effects. One such potentially negative impact is the widespread use of recorded vocalizations, or “playback,” to attract birds of interest, including range-restricted and threatened species. Although playback has been widely used to test hypotheses about the evolution of behavior, no peer-reviewed study has examined the impacts of playback in a birdwatching context on avian behavior. We stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
(32 reference statements)
1
27
0
Order By: Relevance
“…Birds may take time away from foraging, expend energy, or make themselves vulnerable to predation or extra-pair copulations when responding to playback. Rufous Antpittas (Grallaria rufula) and Plain-tailed Wrens (Pheugopedius euophrys) altered their singing behavior in response to playback by increasing vocalizations (Harris and Haskell 2013). Since birds may expend extra energy, become stressed, or divert time from other activities to respond to playback, this method should be used at a minimum to limit such costs, especially for vulnerable species or those for which other behavioral data are being collected (e.g., nest success).…”
Section: Discussionmentioning
confidence: 99%
“…Birds may take time away from foraging, expend energy, or make themselves vulnerable to predation or extra-pair copulations when responding to playback. Rufous Antpittas (Grallaria rufula) and Plain-tailed Wrens (Pheugopedius euophrys) altered their singing behavior in response to playback by increasing vocalizations (Harris and Haskell 2013). Since birds may expend extra energy, become stressed, or divert time from other activities to respond to playback, this method should be used at a minimum to limit such costs, especially for vulnerable species or those for which other behavioral data are being collected (e.g., nest success).…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing birds included those that compared bird diversity and abundance on trails with control sites (Heil et al 2007), in an intensively used area during periods with no visitation and with high visitation (Llavallol et al 2012), bird tolerance of humans in a range of situations (Lambertucci and Speziale 2009;Herrmann et al 2010;Vazquez et al 2011) and the effect of simulated bird watching (using playbacks) on the vocal behaviour of two species of birds (Harris and Haskell 2013).…”
Section: Studies Demonstrating Impactsmentioning
confidence: 99%
“…1700 visitors per day during summer) and no visitation. The study assessing bird tolerance of humans in Tromen Provincial Park in Argentina (Vazquez et al 2011) found that the alert distance of birds varied among species, with some birds affected at distances of 180 m. The study in Tapichalaca Biological Reserve in Ecuador assessing the effects of simulated bird watching using playback (Harris and Haskell 2013) found that playbacks could induce bird habituation and change bird vocal behaviour. Two studies examined the effects of tourism on the Andean Condor in the Patagonian region, including their response to humans and impacts on roost sites (Lambertucci and Speziale 2009;Herrmann et al 2010).…”
Section: Studies Demonstrating Impactsmentioning
confidence: 99%
“…The latter would introduce bias into a followup study (Harris and Haskell 2013). In order to use sound playbacks as an ethical conservation tool, it is important to assess the effect of playback on Crested Guineafowl and establish a protocol (Harris and Haskell 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The latter would introduce bias into a followup study (Harris and Haskell 2013). In order to use sound playbacks as an ethical conservation tool, it is important to assess the effect of playback on Crested Guineafowl and establish a protocol (Harris and Haskell 2013). The aims of the study reported in this paper were (1) to describe the calls of Crested Guineafowl in a social context; (2) to interpret calls in an evolutionary context; and (3) to demonstrate that playbacks can be used to locate and count Crested Guineafowl in small isolated forests.…”
Section: Introductionmentioning
confidence: 99%